Health Care Costs Associated with Acute Asthma: A Prospetive Economic Analysis - Naser Awadh Behbehani; Anton Grunfeld; J Mark FitzGerald (Canadian Respiratory Journal)
OBJECTIVE: To determine the direct and indirect costs associated with the care of acute asthma in an adult teaching hospital.